1989
DOI: 10.1021/la00085a054
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin monolayers and vesicular membranes from calix[6]arenes

Abstract: p-terf-Butylcalix[6]arene produces stable monolayers at the air-water interface having a limiting area of 260 A2/molecule and a film thickness of ca. 10 A. Complete removal of the p-tert-butyl groups affords a unique vesicle-forming surfactant, calix[6]arene, which forms membranes having an apparent thickness of ca. 20 ± 5 A.Phospholipid bilayer membranes have attracted considerable attention over the past 25 years as models for biological membranes, microcapsules, and devices for solar energy conversion.3 45"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 1 publication
5
27
2
Order By: Relevance
“…As in previous studies, multilayer vesicles are not observed. [6,8,9] It must be stressed at this point that, unlike in other studies, the vesicles form spontaneously, i.e., simply after dissolution in aqueous solvents without further treatment, such as sonication etc.…”
Section: Self-assembly In Dilute Solutionsmentioning
confidence: 90%
See 2 more Smart Citations
“…As in previous studies, multilayer vesicles are not observed. [6,8,9] It must be stressed at this point that, unlike in other studies, the vesicles form spontaneously, i.e., simply after dissolution in aqueous solvents without further treatment, such as sonication etc.…”
Section: Self-assembly In Dilute Solutionsmentioning
confidence: 90%
“…As amphiphilic calixarenes can interact with aqueous systems, they are of particular interest for biological and environmental applications, e.g., wastewater treatment, medical diagnosis, and highly sensitive and selective sensors. [2,3] There have thus been some studies on amphiphilic calixarenes in aqueous solution, [1,[4][5][6][7][8][9][10][11][12][13][14][15] but few calixarene-based gels have been reported, [16,17] although such gels could, for example, enable the incorporation of pharmaceutically active compounds into ointments. In the same context, liquid-crystalline calixarenes are interesting, but so far only a few calixarene-based LCs have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was also found for the calix [6]arene without the tert-butyl groups. 30 In this view, it was clear that cations complexation occurred at the spreading, i.e. at very large area values, and the [TCA-M] n+ complexes organized themselves upon compression.…”
Section: Transition Metal Ions Of Hg + Hg 2+ and Pb 2+mentioning
confidence: 97%
“…and the hydrophobic interactions between the tert-butyl residues at the upper side of calixarene. 30 It was worthwhile to emphasize that these molecular cross sections concerned the closely packed monomolecular film, i.e. at the end of the monolayer compression and before the collapse of the monolayer.…”
Section: Transition Metal Ions Of Hg + Hg 2+ and Pb 2+mentioning
confidence: 99%